2016
DOI: 10.15244/pjoes/60492
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Human Activities on Runoff and Sediment of Beiluo River in the Yellow River Based on Paired Years of Similar Climate

Abstract: Climate change and human activities influence runoff and sediment load in an integrated way. However, under similar climate conditions the variability in runoff and sediment load is mainly a result of human activities. In this study, the change trends of runoff and sediment load were detected with linear regression analysis for the Beiluo River on the Loess Plateau, China. The impact of human activities on runoff and sediment was examined under similar weather conditions based on continuous monthly data of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Soil organic carbon density is a certain depth of soil organic carbon storage in the unit area. The calculation formula of organic carbon density (kg·m -2 ) in a soil layer is as follows [18]: (2) …where C j MERGEFORMAT is the SOC content in the layer of soil genus j (g·kg -1 ), D j is the soil bulk density of the layer of soil genus j (g·cm -3 ), E j is soil thickness of the layer of soil genus j (cm), G j is the volume percentage of gravel that is larger than 2 mm of soil genus j, and O j is the bare rock rate in the sampling area of soil genus j (%).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…Soil organic carbon density is a certain depth of soil organic carbon storage in the unit area. The calculation formula of organic carbon density (kg·m -2 ) in a soil layer is as follows [18]: (2) …where C j MERGEFORMAT is the SOC content in the layer of soil genus j (g·kg -1 ), D j is the soil bulk density of the layer of soil genus j (g·cm -3 ), E j is soil thickness of the layer of soil genus j (cm), G j is the volume percentage of gravel that is larger than 2 mm of soil genus j, and O j is the bare rock rate in the sampling area of soil genus j (%).…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%
“…But with the rapid development of the economy, increasing human activities, and climate changes, river ecosystem health degrades day by day in many regions, represent by the sharp imbalance between water resource supply and demand, natural wetland shrinkage, serious river contamination, deductions in estuary runoff, and the disappearance of endemic fish, etc., all influence the sustainable development of nature, the economy, and society [3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…It was observed that water hardness had an adverse effect on washing and rubbing fastness when fabric was dyed with both turmeric and eucalyptus extracts. Therefore, based on this study, the use of mordanting/sequestering agent is suggested to enhance the dye uptake and previous studies also revealed a similar trend that mordanting/sequestering can be used to enhance the color strength and color properties [27][28][29][30][31][32][33][34][35][36], and in view of current environmental pollution [37][38][39][40][41][42][43][44][45][46][47][48][49][50], the natural sources should be preferred to avoid a negative impact on the environment.…”
Section: Color Propertiesmentioning
confidence: 79%
“…The data for extraction for turmeric at different times (30,60, and 90 min) is presented in Fig. 1a with various hard water as compared to control.…”
Section: Resultsmentioning
confidence: 99%